PROTOTIPE PEMROGRAMAN LINIER SEBAGAI MODEL SISTEM PENUNJANG KEPUTUSAN DALAM PENENTUAN JUMLAH OPTIMAL DOSEN DI SEBUAH PERGURUAN TINGGI STUDI KASUS UNIVERSITAS BUDI LUHUR - Ririt Roeswidiah (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2016)
Recruitment and improvement of qualification (level of education and academic positions) of lecturer have to be well planned with proper calculation . This is related to the achievement of the highest grade for the accreditation in terms of the availability of a lecturer in a course of study , is also closely related to the allocation of funds per year that must be provided . Linear programming as one of the models in the Decision Support System, provides alternative optimal solutions for decision makers. Case studies are taken is a matter of planning the development of human resources, especially lecturer Universitas Budi Luhur. Existing conditions are formulated to Linear Programming models. By using the simplex algorithm an application is built to calculate the optimal value, created with the Java programming language , facilitate and accelerate the process of calculating the optimal value of the model.Results of this study are expected to determine the optimal number of lecturer from each study program including the required qualifications, so HRD department do planning & development as well.The results of the prototype test by adapting the software testing standards ISO 9126 concluded that prototype is feasible to use. Keywords : Linear Programming, DSS,Optimal Solutions, Minimum Cost, HRD